Predicting Persistent Disabling Low Back Pain in Veterans Affairs Primary Care Using the STarT Back Tool. Issue 3 (9th November 2020) - Kneeman, Jacob; Battalio, Samuel L.; Korpak, Anna; Cherkin, Daniel C.; Luo, Gang; Rundell, Sean D.; Suri, Pradeep
Abstract : Background: The Subgrouping for Targeted Treatment (STarT Back) is a stratified care approach to low back pain (LBP) treatment. The predictive validity of STarT Back in Veterans Affairs (VA) primary care has not been demonstrated. Objective: To examine the validity of the STarT Back tool for predicting future persistent disabling LBP in VA primary care. Design: Cohort study. Setting: VA primary care in Washington State. Participants: Veterans seeking care for LBP in VA primary care clinics. Interventions: Not applicable. Main Outcome Measures: The STarT Back tool was used to classify Veterans according to their baseline risk group (low vs medium vs high). The primary study outcome, persistent disabling LBP, was defined as a Roland‐Morris Disability Questionnaire (RMDQ) score ≥ 7 at 6‐month follow‐up. Analyses examined discrimination and calibration of the baseline STarT Back risk groups for prediction of persistent disabling LBP at 6‐month follow‐up. Results: Of the study sample, 9% were female and 80% reported longstanding LBP (>5 year duration). Among 538 participants, the baseline STarT Back risk groups were associated with future persistent disabling LBP at 6‐month follow‐up. Within each baseline STarT Back risk group, the proportions with future persistent disabling LBP at 6‐month follow‐up were 54% (low risk), 88% (medium risk), and 97% (high risk). The baseline STarT Back risk groups had useful discrimination (area under the curve [AUC] 0.79) for predicting future persistent disabling LBP, but the proportion of Veterans with persistent disabling LBP at 6‐month follow‐up was substantially higher than that observed in non‐VA primary care settings. Conclusions: The STarT Back risk groups had useful discrimination (AUC = 0.79) for future persistent disabling LBP, but calibration was poor, underestimating the risk of persistent disabling LBP. The STarT Back tool may require updating for use in VA primary care.